Qualidade de vida e autoestima no pós-operatório de um mês em pacientes mastectomizadas com ou sem reconstrução mamária - Alves, Vanessa Lacerda [UNIFESP] (2016)
INTRODUCTION: After the diagnosis and treatment of breast cancer, some women experience physical, social and emotional changes that impact often the quality of life and self-esteem. To assess the quality of life and self-esteem of patients undergoing mastectomies or not breast reconstruction after a month of surgery. Methods: The sample consisted of 90 patients aged less than 30 years, submitted or not to breast reconstruction, and coming from the clinics of plastic surgery and Mastology of the Hospital Pérola Byington. Group 1 (n = 30) composed of the mastectomy patients without breast reconstruction; Group 2 (n = 29) who underwent mastectomy with breast reconstruction; and Group 3 (n = 30) patients without changes in the breasts. For the assessment of quality of life, the instruments validated for use in Brazil European Organization for Research and Tratamento of Cancer Breast Cancer-Specific Quality of Life Questionnaire (EORTC QLQ-C30) EORTC QLQ-C30 and Rosenberg UNIFESP/EPM UNIFESP/EPM Self-Esteem Scale were applied. Results: In the group 1 mastectomized patients without breast reconstruction were observed, 50% had left breast compromise and 1% of both breasts, and in the group 2 mastectomized patients with breast reconstruction, 48.3% had right breast involvement and 2% Of both breasts. There were no changes in the quality of life and self-esteem of patients submitted to mastectomy with or without breast reconstruction after one month of surgery. Conclusion: Women submitted to mastectomy with or without breast reconstruction were not influenced by quality of life and self-esteem after one month of surgery.